Internal conversion and intersystem crossing in α, β-enones: a combination of electronic structure calculations and dynamics simulations. Issue 9 (16th February 2016) - Cao, Jun; Xie, Zhi-Zhong
Abstract : The geometrical constraint of the ring gives rise to a smaller spin–orbital coupling in the singlet–triplet crossing region, resulting in a lower intersystem crossing rate. Abstract : The ab initio electronic structure calculations and CASSCF-based nonadiabatic dynamics simulations have been used to investigate the internal conversion and intersystem crossing process of both trans -acrolein and 2-cyclopentenone in the gas phase. Our calculation results show that relaxation from the Franck–Condon region to an S1 minimum is ultrafast and that the S1 state will dominantly undergo intersystem crossing to triplet states due to the existence of significant barriers to access the S1 /S0 intersection points and of energetically close-lying triplet states. The S1 /T2 /T1 three-state intersection is observed in our dynamics simulations to play an important role in the population of the lowest triplet state, which is consistent with previous suggestions. Although the evolution into triplet states involves a similar path and gives rise to a similar triplet quantum yield for these two molecules, the intersystem crossing rate of 2-cyclopentenone is lower owing to the ring constraint that results in a smaller spin–orbital coupling in the singlet–triplet crossing region. The present theoretical study reproduces the experimental results and gives an explanation about the structural factors that govern the excited-state decay of some types of α, β-enones.